1992
DOI: 10.1677/joe.0.1350485
|View full text |Cite
|
Sign up to set email alerts
|

Site-dependent effects of experimental hypo- and hyperthyroidism on resident macrophages in extraocular muscles of rats: a quantitative immunohistochemical study

Abstract: It has been suggested that the effects of dysthyroidism on resident immunocompetent cells of the extraocular muscles may play a role in the pathogenesis of Graves' ophthalmopathy. The distribution of such cells was therefore studied in extraocular muscles of rats that were made hyper- or hypothyroid by the oral administration of thyroxine or propylthiouracil respectively. Skeletal muscles were studied for comparison. The cell distributions were analysed in cryostat cross-sections subjected to a two-step immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…40 The use of one specific hindlimb muscle, the tibialis anterior, throughout the present study is unlikely to have biased results, as a recent investigation has shown that macrophage numbers were similar in both slow twitch (soleus) and fast twitch (extensor digitorum longus) muscle. 41 Presence of DC in Skeletal Muscle. The demonstration in the present study of irregularly shaped MHC class II + cells in the connective tissue of normal skeletal muscle is strong evidence that these cells are DC according to the generally accepted standards of immunomorphological criteria.…”
Section: Discussionmentioning
confidence: 99%
“…40 The use of one specific hindlimb muscle, the tibialis anterior, throughout the present study is unlikely to have biased results, as a recent investigation has shown that macrophage numbers were similar in both slow twitch (soleus) and fast twitch (extensor digitorum longus) muscle. 41 Presence of DC in Skeletal Muscle. The demonstration in the present study of irregularly shaped MHC class II + cells in the connective tissue of normal skeletal muscle is strong evidence that these cells are DC according to the generally accepted standards of immunomorphological criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Radiochemical purity, i.e., the proportion of free radionuclide, was evaluated by thin layer chroma tography (12). [15][16][17][18][19]. Note the lack of tracer activity in the neck vessels (carotid, jugular veins), as well as in neck muscles.…”
Section: Radiopharmaceutical Evaluation Of the Tracermentioning
confidence: 99%
“…The mechanisms leading to tracer uptake might depend on the primary state of hyperthyroidism. On experimental grounds it has been shown that a hyperthyroid state can induce an increased accumulation of immunocompetent cells along the retrobulbar muscle bundles (17). As a consequence, activated lymphocytes would have the ability to bind octreotide.…”
Section: Comparison Of Scintigraphic and Clinical Datamentioning
confidence: 99%